A novel hybrid bioprocess strategy addressing key challenges of advanced biomanufacturing - Reger, Lucas Nik; Saballus, Martin; Kappes, Annika; Kampmann, Markus; Wijffels, Rene H.; Martens, Dirk E.; Niemann, Julia (Frontiers in Bioengineering and Biotechnology, 2023)
Monoclonal antibodies (mAb) are commonly manufactured by either discontinuous operations like fed-batch (FB) or continuous processes such as steady-state perfusion. Both process types comprise opposing advantages and disadvantages in areas such as plant utilization, feasible cell densities, media consumption and process monitoring effort. In this study, we show feasibility of a promising novel hybrid process strategy that combines beneficial attributes of both process formats. In detail, our strategy comprises a short duration FB, followed by a fast media exchange and cell density readjustment, marking the start of the next FB cycle. Utilizing a small-scale screening tool, we were able to identify beneficial process parameters, including FB interval duration and reinoculation cell density, that allow for multiple cycles of the outlined process in a reproducible manner. In addition, we could demonstrate scalability of the process to a 5L benchtop system, using a fluidized-bed centrifuge as scalable media exchange system. The novel process showed increased productivity (+217%) as well as longer cultivation duration, in comparison to a standard FB with a significantly lower media consumption per produced product (-50%) and a decreased need for process monitoring, in comparison to a perfusion cultivation. Further, the process revealed constant glycosylation pattern in comparison to the perfusion cultivation and has strong potential for further scale-up, due to the use of fully scalable cultivation and media exchange platforms. In summary, we have developed a novel hybrid process strategy that tackles the key challenges of current biomanufacturing of either low productivity or high media consumption, representing a new and innovative approach for future process intensification efforts.